Electrical Stimulation Following Botulinum Toxin A in Children With Spastic Diplegia: A Within-Participant Randomized Pilot Study. (2nd October 2015) - Mudge, Anita; Harvey, Lisa A.; Lancaster, Ann; Lowe, Kevin
ABSTRACT: Aims: To determine whether electrical stimulation (ES) following botulinum toxin A (BoNT/A) injection increases passive extensibility of the hamstring muscles in children with spastic diplegia. Methods: Six children undergoing bilateral BoNT/A injections to the hamstrings participated in this within-participant single blind randomized controlled trial. One leg of each child was randomised to the experimental condition and the other to the control condition. The experimental leg received daily stretch and ES to the hamstrings for 12 weeks, while the control leg received only daily stretch. The primary outcome was passive hamstring extensibility reflected by popliteal angle measured with a standardised torque. Secondary outcomes were two goniometric measures of popliteal angle using the Modified Tardieu Scale (R1 and R2), and parents' perceptions of treatment effectiveness. Outcomes were measured at baseline, 4 weeks, 12 weeks and 6 months. Results: The mean between-group difference (95% CI) at 4 weeks was 2° (−2 to 5) for popliteal angle measured with a standardised torque, favouring the experimental leg. Tardieu results for R1 and R2 were 0° (−4 to 3) and 7° (0 to 14), respectively. Conclusion: ES does not improve passive extensibility of the hamstring muscles at 4 weeks over any possible effects of BoNT/A alone.